Asymptotic equilibrium in quantum system fully coupled simultaneously to mixed fermionic–bosonic heat baths - Hovhannisyan A. A. Arshak; Sargsyan V. V. Vazgen Valerikovich; Adamyan G. G. Gurgen Grigorjevich; Antonenko N. V. Nikolay Viktorovich; Lacroix D. (2020, 2020)
Title screen